Pinewood Derby designs & patterns - Thorne, Troy (DK Publishing, 2007)
Learn the secrets to crafting cool cars for the Pinewood Derby. Includes designs, detailed measured drawings and cutting patterns, tips and techniques for peak performance and safety.